2021
DOI: 10.1186/s12911-021-01440-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient triage system for supporting the operation of dispatch centres and rescue teams

Abstract: Background The Thai medical application for patient triage, namely Triagist, is an mHealth application designed to support the pre-hospital process. However, since the functions of the application that are necessary for the pre-hospital process have been found not to be fully developed, the addition of a back-end system has been considered to increase its performance and usability. Objective To determine the ability of the previous version to effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In the search for the apps identified in the relevant papers on the Google Play Store platform, only the "TRIAGIST" app proposed by the studies was found. [31,32] and Major Trauma Triage Tool presented at [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the search for the apps identified in the relevant papers on the Google Play Store platform, only the "TRIAGIST" app proposed by the studies was found. [31,32] and Major Trauma Triage Tool presented at [22].…”
Section: Discussionmentioning
confidence: 99%
“…Following the same objective of improving prehospital patient triage using mobile applications, Sutham et al [ 79 ] developed an app to classify patients based on initial dispatch codes and criteria-based dispatch. In this case, the authors found the app evaluation to be faster and more effective than regular triage in non-trauma scenarios [ 79 , 80 ]. Furthermore, among other apps created for more specific purposes, FAST-ED helps prehospital emergency services to triage patients with cerebrovascular events to an appropriate hospital [ 81 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…The process of EMS operations in Khon Kaen Province starts with emergency patient calls for help at the emergency services 1669 call center; the call taker and dispatcher will take a preliminary history to assess the severity of the patients and divide the patients into three categories (red, yellow, and green) following the Thailand emergency medical triage protocol and criteria-based dispatch. 19,20 The dispatcher then orders the EMS operation. After that, the EMS unit of Srinagarind Hospital receives that order, and the EMS operation will begin.…”
Section: Data Collection and Outcome Measurementmentioning
confidence: 99%